How manipulating task constraints in small-sided and conditioned games shapes emergence of individual and collective tactical behaviours in football: A systematic review - Ometto, L.; Vasconcellos, F.; Cunha, F. A.; Teoldo, I.; Raphael B Souza, C.; Dutra, M. B.; O'Sullivan, M.; Davids, K. (International Journal of Sports Science & Coaching, 2018)
Background: Small-Sided and Conditioned Games are characterised by modifications of field dimensions, number of players, rules of the game, manipulations used to shape the key task constraints that performers need to satisfy in practice. Evidence has already demonstrated the importance of designing practice to enhance understanding of tactical behaviours in football, but there is a lack of information about how coaches can manipulate task constraints to support tactical learning. Objective: To investigate which task constraints have been most often manipulated in studies of SSCGs; and what impact each manipulation had on emerging tactical behaviours, technical-tactical actions, and positional relationships between players. Methods: PubMed, Web of Science, Scielo, and Academic Google databases were searched for relevant reports without time limits. The criteria adopted for inclusion were: a) studies performed with football players; b) studies that included SSCGs as an evaluation method; c) studies that investigated tactical behaviours in SSCGs; and d), articles in English and Portuguese. Results: The electronic database search included 24 articles in the review. Of these, five manipulated field dimensions, six manipulated number of players involved, five manipulated field dimensions and number of players, five used different scoring targets, two altered the number of players and scoring target, and one manipulated the number of players, field dimension, and scoring target. Conclusion: Among the task constraints analyzed in this systematic review, manipulation of number of players and playing field dimensions concomitantly occurred most frequently.